2022
DOI: 10.1155/2022/8020938
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Superabsorbent Polymers to Growth and Yield of African Leafy Vegetables

Abstract: Superabsorbent polymers (SAPs) have been used as water-saving materials for limited irrigation water resources in arid and semi-arid areas. The purpose of this study was to optimize SAP application dosage and irrigation intervals on the growth of African leafy vegetables (ALVs) under greenhouse conditions. A factorial experiment was conducted under greenhouse conditions to determine the optimal SAP application, dosage, and irrigation intervals for the growth and production of African leafy vegetables. Two spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In the study by Okello et al [64] two varieties of nightshade measurements on plant height and S. scabrum variety exhibited taller plants (40.17 cm) under the greenhouse cultivation with different levels of irrigation. Benard et al [71] reported the highest plant height 51 cm of African nightshade grown in the greenhouse where different concentration of superabsorbent polymers was applied. On the other hand, open-field plant height in our study resulted in a lower height of 52.67 cm compared to the greenhouse.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Okello et al [64] two varieties of nightshade measurements on plant height and S. scabrum variety exhibited taller plants (40.17 cm) under the greenhouse cultivation with different levels of irrigation. Benard et al [71] reported the highest plant height 51 cm of African nightshade grown in the greenhouse where different concentration of superabsorbent polymers was applied. On the other hand, open-field plant height in our study resulted in a lower height of 52.67 cm compared to the greenhouse.…”
Section: Discussionmentioning
confidence: 99%